Global liquidity, world savings glut and global policy coordination - Ansgar Belke; Daniel Gros (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The global imbalances of the 2000s and the recent global financial crisis are intimately connected. Both originate in the combination of economic policies adopted by the two key economies, the US and China. Global financial markets served as a transmission belt, both during the boom as during the bust. In the US, the interaction among the Fed's monetary stance, global real interest rates, distorted incentives in credit markets, and financial innovation created the mix of conditions which first drove growth, but then made the US the epicenter of the global financial crisis. Exchange rate and other economic policies followed by emerging markets such as China and the oil-exporting countries contributed to the US ability to borrow cheaply abroad and thereby finance its unsustainable housing bubble during the upswing. But we find that the key drivers of asset prices are global liquidity conditions. Central banks flooded the markets with ample liquidity. Mopping up this excess liquidity will be one major task for central banks worldwide, which needs to be done in a coordinated fashion. Moreover, our analysis has shown that liquidity will first show up in asset price inflation and only later in consumer goods inflation. This renders it difficult for central bank to exit from their current very expansive monetary policy stance if they continue to focus only on price stability.
Keywords: E21; E43; E52; F32; F42; Q43; 330; Asset prices; China; current account adjustment; global liquidity; oil prices; savings glut; monetary policy; policy coordination; Geldpolitik; Internationale wirtschaftspolitische Koordination; Sparen; Gesamtwirtschaftliche Liquidität; Zahlungsbilanzungleichgewicht; Vermögen; Inflation; Finanzmarktkrise; Welt; USA; China